2019
DOI: 10.3390/vetsci6030065
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Cardiac Hemangiosarcoma in a 6 Year Old Wheaten Terrier Mix

Abstract: A 6 year old Wheaten Terrier mix with a history of collapse and lethargy was referred for evaluation of pericardial effusion. The echocardiogram identified pericardial effusion and a right auricular mass. No sign of metastasis was noted at this time in thoracic radiographs and abdominal ultrasounds. The patient underwent the right auriculectomy via right lateral thoracotomy. Several metastatic masses were located in the visceral aspect of the pericardium at the time of surgery and were all excised. The right a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…The clinical signs of affected animals include lethargy, apathy, anorexia, weakness, weight loss, emesis, exercise intolerance, dyspnea, cough, syncope, and collapse [ 15 , 28 , 178 , 179 , 180 , 183 , 188 , 189 , 190 , 191 ]. Physical examination revealed muffled cardiac and pulmonary auscultation, arrhythmias, weak pulse, jugular distention, pale mucous membranes, abdominal distension, dehydration, tachypnea, and tachycardia [ 5 , 15 , 28 , 179 , 180 , 189 , 190 ].…”
Section: Cardiac Hemangiosarcomamentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical signs of affected animals include lethargy, apathy, anorexia, weakness, weight loss, emesis, exercise intolerance, dyspnea, cough, syncope, and collapse [ 15 , 28 , 178 , 179 , 180 , 183 , 188 , 189 , 190 , 191 ]. Physical examination revealed muffled cardiac and pulmonary auscultation, arrhythmias, weak pulse, jugular distention, pale mucous membranes, abdominal distension, dehydration, tachypnea, and tachycardia [ 5 , 15 , 28 , 179 , 180 , 189 , 190 ].…”
Section: Cardiac Hemangiosarcomamentioning
confidence: 99%
“…Patients complaining of pericardial effusion should undergo pericardiocentesis as the first intervention to allow for patient stabilization in addition to assisting in the diagnostic investigation, especially in cases that progress to metastasis in the pericardium. However, drainage of pericardial effusion has palliative purposes, and in the absence of definitive treatment, it becomes recurrent [ 15 , 178 , 187 , 191 ].…”
Section: Cardiac Hemangiosarcomamentioning
confidence: 99%
“…However, several studies have shown that surgical resection alone can provide an MST of 42-86 days, whereas surgery with chemotherapy can increase MST to 116-189 days (11,19,21). In cases where incomplete resection or metastasis is present, the addition of chemotherapy can still provide a significant increase in survival time, with a reported survival time of 177 and 318 days, respectively (1,4). These findings demonstrate the benefits of surgical resection and chemotherapy in the treatment of cardiac HSA.…”
Section: Discussionmentioning
confidence: 75%
“…However, pericardiectomy alone does not prolong survival (15). Studies have shown that adjuvant chemotherapy with doxorubicin after tumor removal significantly increases the median survival time in dogs with cHSA, with reported survival times of up to 318 days after right atrial mass resection and chemotherapy (1,11,21).…”
Section: Introductionmentioning
confidence: 99%
“…It wasn't until surgical exploration that several metastatic masses were seen in the pericardium and were also removed. 16 Another case study revealed a similar pattern of nonspecific gastrointestinal symptoms with no apparent cause in a daschund with primary colonic HSA24. Following two previous visits, each of which consisted of diagnostic screenings with no significant findings reported either time, the patient represented in critical condition with decreased mobility, increased melena and hematochezia, pale mucous membranes and weak femoral pulses.…”
Section: Presentationmentioning
confidence: 86%